Identifikasi Elemen Logistik Kota Batam Sebagai Hub Logistik Asean - Arifa Fikriya Zaharol Muna (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Riau, 2020)
Batam City is one of cities that has the potential to be developed into an ASEAN Logistics Hub. Geographical conditions in Indonesia's borders also locations close to the Malacca Strait make Batam City much traversed by ships and become one of the busy logistics lanes. In planning the development of logistics quality, it is necessary to know the priority logistical elements that are the fulcrum. This study uses primary data obtained from interviews and secondary data from journals then analyzed with qualitative descriptive methods. The data obtained will be processed by triangulation, reduction, presentation of data and drawing conclusions. The infrastructure element is a priority element that must be developed to increase the capacity and capability of Batam City as the ASEAN Logistics Hub. These elements are included in the elements of strategic, tactical and operational planning in the form of customer service, availability of storage areas and easy access including digital logistics program development. In addition these elements are closely related to the ease of delivery, logistics, tracking and tracing services and to accelerate the delivery time which is managed and developed by BP Batam, Disperindag, PT Pelindo, MRO Hang Nadiem and PT Citra Shipyard. The customs or legal element is managed directly by Bea Cukai which has legal policies and the identity of the traffic of goods. The identification of logistics elements can be a measurement point for the development of Batam City as an ASEAN Logistics Hub.